Incomplete Arctic Sea‐Ice Recovery Under CO2 Removal and Its Effects on the Winter Atmospheric Circulation - Hao Yu; James A. Screen; Mian Xu; Stephanie Hay; Weiteng Qiu; Jennifer L. Catto (Geophysical Research Letters)
Abstract This study explores the response of Arctic sea ice to CO2 removal and its subsequent effects on the winter Northern Hemisphere atmospheric circulation. Using multimodel ensembles from the Carbon Dioxide Removal Model Intercomparison Project, we find that most models display incomplete Arctic sea‐ice recovery when CO2 is stabilized back at preindustrial levels, with a deficit of sea‐ice area of around 1 million km2. This sea‐ice deficit is associated with residual equatorward‐shifted wintertime midlatitude jets. Sea‐ice perturbation experiments from the Polar Amplification MIP provide evidence of a causal influence of residual sea‐ice loss on the atmospheric circulation. Model uncertainty in the magnitude of the residual North Atlantic jet shift can be largely explained by the relative magnitudes of residual Arctic and tropical warming across the models. These findings suggest that Arctic sea‐ice loss is not fully reversible after CDR, which leads to residual changes in the mid‐latitude atmospheric circulation.